PERLINDUNGAN HUKUM BAGI ANAK KORBAN PENELANTARAN BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 ATAS PERUBAHAN UNDANG-UNDANG N0MOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA DUMAI - Agafe Marulytua Ambarita; Erdianto Effendi; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Kids are the future generation who need special legal protection different from adults, due to their physical and mental reasons immature and mature. Article 28B paragraph (2) of the Constitution of the Republic of Indonesia 1945 provides that, "Every child has the right to survival, growth and development, and is entitled to protection from violence and discrimination". But the fact is, there are many children whose rights are unfulfilled to date. As for the purpose of the author of this thesis, namely: first, to determine the legal protection for child victims of neglect under Act No. 35 of 2014 on the Amendment of Act No. 23 of 2002 on Protection of Children in Legal Jurisdiction City Police Dumai, both , to find out the bottlenecks in implementation of Legal Protection Against for Children Victims of Neglect under Law No. 35 of 2014 on the Amendment of Act No. 23 of 2002 on Protection of Children in jurisdictions City Police Dumai, thirdly, to know the efforts made by the parties Police overcome the obstacles in the implementation of the legal protection of the child victims of neglect at the Regional Police Dumai City. This type of research is classified as socio-juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted on the Law of Police Dumai, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data tertiary, data collection techniques in this study by interview, and literature study. From the results, it can be concluded that, first, the legal protection for child victims of neglect at City Police Jurisdiction Dumai not run in accordance with Act No. 35 of 2014 on the Amendment of Act No. 23 of 2002 regarding Child Protection. This makes people reporting laporanya not processed by the police so as not achieving the legal protection of victims of neglect, second, obstacles in the implementation of legal protection of child victims of neglect in Jurisdiction City Police Dumai is the resistance that the arrival of the Police of the resort dumai, limitations facilities and infrastructure and the obstacles that come from the public complainant, third, the efforts of the police to Dumai overcome the obstacles in the implementation of the legal protection of the child victims of neglect at the Regional Police Dumai City is to maximize the performance of Police Dumai.Keywords: Legal Protection-Children-Victims of Neglect